PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 11 PADANG - Cahyadi, Nadia; Aima, Zulfitri; Mardiyah, Ainil (Pendidikan Matematika, 2014)
ABSTRACTLearning methode beetwen teacher and students that doesnât make students learn into a group, make a comprehension of mathematics studentâs concept in a lower rank. According to this, by implementing cooperative learning Team Assisted Individualization (TAI) type which is expected can help the comprehension of mathematics studentâs concept. This research is aims to know the comprehension of mathematics studentâs concept by implementing cooperative learning Team Assisted Individualization (TAI) type better than comprehension of mathematics students concept by using conventional learning. This research is an experimental study with Randomized Control Group Only Design. Sampling select randomly to class VIIIa as experiments class and class VIIIb as control class. Instrument of this research is comprehension of mathematics students concept from essay test which is test reliability is 0.92. Based on the results of data analysis with testÂ  t Â³ Â retrieved 4,440 â¥ 1.6966 then accepted . So, it can be concluded that comprehension of mathematics students concept by implementing cooperative learning Team Assisted Individualization (TAI) type be tter than comprehension of the mathematics studentâs concept by using conventional learning.Â